2012
DOI: 10.1007/s00421-012-2387-8
|View full text |Cite
|
Sign up to set email alerts
|

Stunting delays maturation of triceps surae mechanical properties and motor performance in prepubertal children

Abstract: Malnutrition can lead to possible irreversible consequences in the development of muscle function and some of them are yet poorly characterized. The present study evaluated the mechanical properties of the triceps surae and motor performance in stunted (S) and eutrophic (E) prepubertal children (9 years ± 6 months). Height-for-age ratio was used as indicator of stunting due to early malnutrition, according to the World Health Organization. Torque was determined by maximal voluntary contractions (MVC) and muscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
12
0
3
Order By: Relevance
“…As the main predictor of BMR is the FFM, a lower lean tissue mass may be implicated within the reduction of BMR and in body fat accumulation 17 . It was demonstrated that early malnourished children (9 years ± 6 months) presented lower capacities to develop force under voluntary or induced conditions 18 . Lower BW is linked to reduced motor performance including muscle strength, muscle endurance and cardiorespiratory fitness in children and adolescents 19 .…”
Section: Introductionmentioning
confidence: 99%
“…As the main predictor of BMR is the FFM, a lower lean tissue mass may be implicated within the reduction of BMR and in body fat accumulation 17 . It was demonstrated that early malnourished children (9 years ± 6 months) presented lower capacities to develop force under voluntary or induced conditions 18 . Lower BW is linked to reduced motor performance including muscle strength, muscle endurance and cardiorespiratory fitness in children and adolescents 19 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Motor performance encompasses several physical fitness components (cardiorespiratory, muscle strength, muscle endurance, body composition, agility, and flexibility) and motor coordination (fine and gross coordination).…”
mentioning
confidence: 99%
“…8 Motor performance involves the integration of the central nervous system and the skeletal-muscle system to arrange the action of muscles, joints, and limbs to develop adequate strength, speed, and resistance for an intended motor task. 9 Motor performance encompasses several physical fitness components (cardiorespiratory, muscle strength, muscle endurance, body composition, agility, and flexibility) and motor coordination (fine and gross coordination). 10 Motor performance and gross motor coordination seem to be directly associated with regular physical activity and body composition in children and adolescents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a nutritional related deficiency in tendon structure mineralization can hold for the lower passive stiffness in the children of the S group. Such adaptive responses suggest that the MT stiffness index evolution in stunted prepubertal children is delayed, being similar to younger eutrophic counterparts (Lambertz et al, 2003;Paiva et al, 2012).…”
Section: Intrinsic Adaptation Of the Musculotendinous Unitmentioning
confidence: 92%